Not with a Bang, but a Whimper: Sherley v. Sebelius - Davis, Dena S. (The Hastings Center report, 2013)
After a tortuous legal process that resembled nothing so much as a game of chutes and ladders, on August 24, 2012, the United States Court of Appeals for the District of Columbia Circuit decided in favor of the Department of Health and Human Services' position that human embryonic stem cell research is not research that harms embryos, and therefore is not a violation of the Dickey-Wicker Amendment. Bioethicists have been following this case because of our interest in the ethics and politics of embryonic stem cell research, but the final decision hinged largely on a series of rather arcane points of law and procedure.